2013
DOI: 10.1007/s00109-013-1069-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal steroid treatment on the developing immune system

Abstract: Betamethasone administered to the mother before birth reaches the fetal thymus. Prenatal betamethasone results in massive loss of developing thymocytes. The effects of betamethasone on thymus development are visible for several days. Human thymocytes are also sensitive to low doses of betamethasone. Altered thymocyte development around birth may have an effect on the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…It was reported that prenatal TCDD could promote the thymocyte apoptosis and finally resulted in thymus atrophy in offspring48. In addition, prenatal betamethasone exposure could induce the apoptosis of DP, and reduce the proliferation of immature thymocytes49. In our study, the results of both TEM and flow cytometry showed that the total apoptosis rate of fetal thymocyte in nicotine group was increased.…”
Section: Discussionsupporting
confidence: 51%
“…It was reported that prenatal TCDD could promote the thymocyte apoptosis and finally resulted in thymus atrophy in offspring48. In addition, prenatal betamethasone exposure could induce the apoptosis of DP, and reduce the proliferation of immature thymocytes49. In our study, the results of both TEM and flow cytometry showed that the total apoptosis rate of fetal thymocyte in nicotine group was increased.…”
Section: Discussionsupporting
confidence: 51%
“…route, and lymphocyte suppression was also comparable for the BetaP plus BetaA. A concern for clinical use is that corticosteroids have large effects on the developing immune system of the fetus that could alter immune function in the child and adult …”
Section: Discussionmentioning
confidence: 87%
“…A concern for clinical use is that corticosteroids have large effects on the developing immune system of the fetus that could alter immune function in the child and adult. [33][34][35] The study has limitations as we studied only fasted healthy Indian-Asian women. Extrapolation to other populations of different racial backgrounds, a wide range of BMI, nonfasted, and pregnant women must be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of the later were shown to cause apoptosis of thymocytes resulting in the gland's involution . The thymus was shown to reduce in size after exposure to synthetic steroids (Betamethasone) in fetal mouse and ovine models and in human thymocytes …”
Section: Changes In Thymus Sizementioning
confidence: 99%